A software model for distance learning of idiomatic music expressivity - Solti, Endre; Fornari, José (Revista Hipótese, 2022)
Recent studies in linguistics and neuroscience suggest that music has characteristics in common with verbal language. In this sense, this work, coming from a doctoral project in progress by the author, proposes the creation of an application for mobile devices (app) for the musical teaching of musical expressiveness at a distance (DE) on the electric guitar or guitar, based on strategies of spoken and written language learning. The application or app will be developed from a computational representation system called "Fraseado", whose theoretical basis will be treated in this work.